2011
DOI: 10.1074/jbc.m110.194027
|View full text |Cite
|
Sign up to set email alerts
|

H3K36 Methylation Antagonizes PRC2-mediated H3K27 Methylation

Abstract: H3K27 methylation mediated by the histone methyltransferase complex PRC2 is critical for transcriptional regulation, Polycomb silencing, Drosophila segmentation, mammalian X chromosome inactivation, and cancer. PRC2-mediated H3K27 methylation can spread along the chromatin and propagate the repressive chromatin environment; thus, chromatin components that antagonize the activity of PRC2 are important for restraining Polycomb silencing. Here we report that in HeLa cells, H3 histones unmethylated at Lys-36 are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

64
472
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 478 publications
(542 citation statements)
references
References 43 publications
64
472
2
4
Order By: Relevance
“…S1), so the SDG8-ELF6 interaction is probably independent of transcriptional elongation. The mutually exclusive pattern between H3K27me3 and H3K36me3 has been found in several other systems (2,35,36) and could be explained by the observation that H3K36me3 can inhibit PRC2 activity (37). Our data here provide another possible explanation: that H3K36me3 antagonizes PRC2 repression by codelivering H3K27 demethylase activity with the H3K36 methyltransferase.…”
Section: Resultsmentioning
confidence: 49%
“…S1), so the SDG8-ELF6 interaction is probably independent of transcriptional elongation. The mutually exclusive pattern between H3K27me3 and H3K36me3 has been found in several other systems (2,35,36) and could be explained by the observation that H3K36me3 can inhibit PRC2 activity (37). Our data here provide another possible explanation: that H3K36me3 antagonizes PRC2 repression by codelivering H3K27 demethylase activity with the H3K36 methyltransferase.…”
Section: Resultsmentioning
confidence: 49%
“…Candidate COOLAIR interacting H3K36 methyltransferase enzymes could be EARLY FLOWERING IN SHORT DAYS (EFS) (24,25), AtPAF1c-mutant VIP4 methyltransferase (26), or Ash1 homologs. Reports have shown that the conserved Trithorax group protein Ash1 is an H3K36-specific dimethylase (27,28). In Arabidopsis, the Ash1 homolog SDG4 was shown to methylate H3K4 and H3K36 (29).…”
Section: Discussionmentioning
confidence: 99%
“…We, and others, have previously reported that H3K36 methylation rarely coexists with H3K27me3 on the same H3 polypeptides (19,38), suggesting that these two modifications may antagonize each other. Indeed, the catalytic activity of PRC2 is inhibited in cis by di-or tri-methylation at lysine 36 of the same H3 histones (19,39,40).…”
mentioning
confidence: 99%
“…Indeed, the catalytic activity of PRC2 is inhibited in cis by di-or tri-methylation at lysine 36 of the same H3 histones (19,39,40). However, H3K27me3 does not inhibit * This work was supported by Chinese Ministry of Science and Technology FIGURE 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation